Seasonal variation and light absorption property of carbonaceous aerosol in a typical glacier region of the southeastern Tibetan Plateau - H. Niu; H. Niu; S. Kang; S. Kang; S. Kang; H. Wang; R. Zhang; R. Zhang; R. Zhang; X. Lu; Y. Qian; R. Paudyal; et al. (Atmospheric Chemistry and Physics, 2018)
Deposition and accumulation of light-absorbing carbonaceous aerosol on glacier surfaces can alter the energy balance of glaciers. In this study, 2 years (December 2014 to December 2016) of continuous observations of carbonaceous aerosols in the glacierized region of the Mt. Yulong and Ganhaizi (GHZ) basin are analyzed. The average elemental carbon (EC) and organic carbon (OC) concentrations were 1.51±0.93 and 2.57±1.32 µg m−3, respectively. Although the annual mean OC ∕ EC ratio was 2.45±1.96, monthly mean EC concentrations during the post-monsoon season were even higher than OC in the high altitudes (approximately 5000 m a. s. l. ) of Mt. Yulong. Strong photochemical reactions and local tourism activities were likely the main factors inducing high OC ∕ EC ratios in the Mt. Yulong region during the monsoon season. The mean mass absorption efficiency (MAE) of EC, measured for the first time in Mt. Yulong, at 632 nm with a thermal-optical carbon analyzer using the filter-based method, was 6.82±0.73 m2 g−1, comparable with the results from other studies. Strong seasonal and spatial variations of EC MAE were largely related to the OC abundance. Source attribution analysis using a global aerosol–climate model, equipped with a black carbon (BC) source tagging technique, suggests that East Asia emissions, including local sources, have the dominant contribution (over 50 %) to annual mean near-surface BC in the Mt. Yulong area. There is also a strong seasonal variation in the regional source apportionment. South Asia has the largest contribution to near-surface BC during the pre-monsoon season, while East Asia dominates the monsoon season and post-monsoon season. Results in this study have great implications for accurately evaluating the influences of carbonaceous matter on glacial melting and water resource supply in glacierization areas.